Effects of using complex training method on muscular power among competitive male weightlifters / Garry Kuan, Wan Firdaus and Oleksandr Krasilshchikov - Garry, Kuan; Wan, Firdaus; Oleksandr, Krasilshchikov (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2018)
Weightlifting is a sport that requires both dynamic strength and power. Until today, weightlifting coaches are still exploring different training modes in an attempt to enhance both muscular strength and power of the competitive weightlifters. Research has shown that the use of the “right” training method could further provide knowledge on such effect for competitive weightlifters (Storey & Smith, 2012). Thus, the aim of this study was to investigate the effects of using the complex training method (applicable to weightlifting) compared to traditional resistance training on muscular strength among male competitive (state level) weightlifters. Seventeen male competitive weightlifters were randomly assigned into 2 groups: experimental group (Complex Training; n = 9), and control group (Traditional Resistance Training; n = 8). All participants trained for 6 weeks (2 sessions per week) with the total training volume equated between both groups. Participants underwent pre-test and post-test including the anthropometric measurements (height, body weight, and body fat) and lower body strength (CMVJ test) and overall body power (medicine ball throw test) parameters. The results showed that there was a significant increase from pre- to post-test in CMVJ average power t(8) = -4.98; p = .001 and t(7) = -3.99; p = .005), CMVJ height t(8) = -3.17; p = .01 and t(7) = -3.95; p = .006) and medicine ball throw distance t(8) = -12.26; p = .001 and t(7) = -6.13; p = .001) in experimental and control groups respectively. Significant difference (p < .05) was observed in CMVJ average power (5.04 ± 2.61 versus 1.64 ± 1.16), CMVJ height (13.23 ± 7.29 versus 6.70 ± 4.80) and medicine ball throw distance improvements (0.87 ± 0.21 versus 0.46 ± 0.21) between the complex training group and control group respectively at post-test. In conclusion, the use of complex training method showed more superior in enhancing muscular power compared to traditional resistance training after 6 weeks of intervention.